Gender differences in access to information and adoption of climate-smart agriculture practices in Uganda: The role of women's empowerment - Khan, Rashid; Bosch, Christine; Kato, Edward; Bryan, Elizabeth; Birner, Regina; Daum, Thomas; Gupta, Saurabh; Ringler, Claudia (2021)
Prepared by Rashid Khan , Christine Bosch, Edward Kato, Elizabeth Bryan , Regina Birner, Thomas Daum, Saurabh Gupta, and Claudia Ringler